2021
DOI: 10.1037/adb0000739
|View full text |Cite
|
Sign up to set email alerts
|

Contextual influences on simultaneous alcohol and cannabis use in a predominately white sample of college students.

Abstract: Objective: Simultaneous alcohol and cannabis (i.e., marijuana [SAM]) use is highly prevalent among young adults and college students and associated with a number of negative consequences compared to single substance use. The current study examined socio-contextual factors (e.g., physical, situational, social) associated with SAM use versus cannabis-only versus alcohol-only use. Method: Data were collected from college student SAM users (N = 313, 53% women, M age = 19.79; 74% White; 10% Hispanic/Latinx) who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2021
2021
2122
2122

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…However, recent work has found that social context (i.e., being with others versus being alone) predicts co-use compared to single substance use in both adolescent and young adult samples. 37 , 68 , 69 Location of use also predicts co-use over single substance use, in that simultaneous use is more likely to occur at a friend’s place, at a party, and when people are around. 69 More work is needed to examine how complex contextual (e.g., social, location, situational) factors interact to predict co-use in more diverse samples, and in treatment-seeking samples, as this may help to inform intervention and prevention efforts.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent work has found that social context (i.e., being with others versus being alone) predicts co-use compared to single substance use in both adolescent and young adult samples. 37 , 68 , 69 Location of use also predicts co-use over single substance use, in that simultaneous use is more likely to occur at a friend’s place, at a party, and when people are around. 69 More work is needed to examine how complex contextual (e.g., social, location, situational) factors interact to predict co-use in more diverse samples, and in treatment-seeking samples, as this may help to inform intervention and prevention efforts.…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers examined contexts associated with SAM use. 21 , 25 , 31 , 38 , 51 54 Overall, context was an important correlate associated with SAM use across samples (community, treatment seeking) and designs (cross-sectional, event-level). However, findings on specific settings were mixed.…”
Section: Resultsmentioning
confidence: 98%
“…Associations between contexts and SAM use seemed to differ based on participants’ ages as well as whether the comparison day was alcohol-only or marijuana-only use. 51 , 54 One paper found that college students were more likely to engage in SAM use—compared to alcohol-only and marijuana-only use—at a friend’s place. 54 These students were also more likely to engage in SAM use at parties and less likely to engage in SAM use at a bar or restaurant relative to alcohol use only.…”
Section: Resultsmentioning
confidence: 99%
“…While several diary studies have examined day-level consequences associated with alcohol and cannabis co-use (e.g., Lee et al, 2020; Linden-Carmichael, Van Doren, et al, 2020; Mallett et al, 2019; Sokolovsky et al, 2020), relatively less attention has been placed on antecedents to use. Toward this end, Gunn et al (2021) examined day-level physical, situational, and social characteristics associated with SAM use relative to days with only alcohol or only cannabis use among a sample of 18–24 year olds currently attending college. Findings revealed that parties, friends’ homes, and being around more people were associated with SAM use occasions relative to single-substance use occasions.…”
Section: Patterns Predictors and Short- And Long-term Outcomes Of Co-usementioning
confidence: 99%